Magnetically recoverable 2‐(aminomethyl)phenols‐modified nanoparticles as a catalyst for Knoevenagel condensation and carrier for palladium to catalytic Suzuki coupling reactions. (12th July 2020) - Wang, Gongshu; Ding, Zhiqiang; Meng, Lingxin; Yan, Guiyang; Chen, Zhangpei; Hu, Jianshe
Abstract : A class of magnetic nanoparticles modified by 2‐(aminomethyl)phenols has been successfully designed and synthesized as a reusable catalyst for Knoevenagel reaction. What's more, such nanomaterial also proved as suitable carrier for immobilization of palladium nanoparticles and the obtained composite exerted potent catalytic activity in Suzuki coupling reactions. Both of the (aminomethyl)phenols‐modified nanoparticles and its related palladium nanocatalyst could be easily separated and reused for several consecutive runs by magnetic decantation without significant loss of their catalytic efficiency. Abstract : 1. 2‐(Aminomethyl)phenols were introduced to the synthesis of recyclable nanocatalysts. 2. The core‐shell hybrid NPs proved as efficient catalysts for Knoevenagel reactions. 3. Immobilization of palladium NPs could promote the Suzuki coupling reactions.